Improved technologies at restoring crankshafts operational integrity for diesel vehicle destination - Демин, Андрей Юрьевич; Тимофеева, Лариса Андреевна; Тимофеев, Сергей Сергеевич; Ягодинский, Евгений Сергеевич (Eastern-European Journal of Enterprise Technologies, 2014)
Most of the known methods, applied in production for hardening and lifetime restoration of main journals and crankpins are used only in the restoration process of small crankshaft journals (in automobile and tractor engines). Most standard hardening techniques and traditional wear-resistant coating technologies do not provide the required level of increasing wear resistance and fatigue strength of parts simultaneously. Complex technology for restoring the operational integrity of transport diesel engine crankshafts is considered in the paper. Its feature is that the product is plunged into the solution of silicate salts after the traditional heat treatment and HFC hardening that leads to the antifriction layer formation on the treated surface. Using this complex of operations within one technological cycle will allow improving the surface operational properties of main journals and crankpins, and, as a result, the repair technology efficiency of transport diesel engine crankshafts as a whole.